Risk Factors Dengue Fever in an Endemic Area in Sikka, Indonesia; A Case-Control Study - Avelinus Serbianus Nong Erwin; Nur Nasry Noor; Wahiduddin; A. Arsunan Arsin; Hasanuddin Ishak; Andi Julia Junus (National Journal of Community Medicine, 2024)
Background: Dengue fever is a serious health problem that burdens public health and the economy. The aims to analyzing the risk factors for dengue fever in endemic areas in Sikka Regency.